Role of promoters in copper chromite catalysts for hydrogenolysis of glycerol - Mane, R. B.; Ghalwadkar, Ajay A.; Hengne, Amol M.; Suryawanshi, Y. R.; Rode, C. V. (Catalysis Today, 2011)
Various copper chromite catalysts with and without promoters were prepared by simultaneous co-precipitation and digestion technique and the role of promoters (Al, Ba and Zn) was investigated for hydrogenolysis of glycerol to 1,2-propylene glycol (1,2-PG) in both batch and continuous operations. Among various promoters studied, copper chromite catalyst with Ba as a promoter showed the highest activity and selectivity of 85% to 1,2-PG. This catalyst was found to be active for more than 800 h in a continuous operation also. Ammonia TPD results showed that barium promoted copper chromite catalyst had the highest acidity which facilitates the dehydration of glycerol to acetol which is the first step in hydrogenolysis of glycerol to 1,2-PG. The effect of barium content and variation in the promoters combination was also studied. (C) 2010 Elsevier B.V. All rights reserved.
1st Joint International Conference of the 8th Tokyo Conference on Advanced Catalytic Science and Technology/5th Asia Pacific Congress on Catalysis, Sapporo, JAPAN, JUL 18-23, 2010
Keywords: 1; 2-Propylene glycol; Acetol; Ammonia TPD; Glycerol hydrogenolysis; Surface acidity

Reductive cyclization of levulinic acid to gamma-valerolactone over non-noble bimetallic nanocomposite - Kadu, Brijesh S.; Hengne, Amol M.; Biradar, Narayan S.; Rode, Chandrashekhar V.; Chikate, Rajeev C. (Industrial & Engineering Chemistry Research, 2016)
Bimetallic nanoparticles have diverse applications in catalytic processes owing to the differences in individual properties that contribute to their increased catalytic activity. To further improve the efficiency, they are dispersed in an inert support that enhances the catalytic activity toward organic transformations. In this study, we report simple, facile, and cost-effective chemical route for the fabrication of nanocomposites with Fe-Ni bimetallic nanoparticles supported on montmorillonite (MMT) possessing variation in the Fe and Ni content. These composites are characterized with X-ray diffraction, transmission electron microscopy surface area, and NH3-TPD. Fe Ni bimetallic nanoparticles are well-dispersed within MMT structure having particle sizes of about 30-40 nm. Among various compositions of Fe-Ni/MMT catalysts, composite with 25% Fe and 25% Ni exhibits >99% LA conversion with 98% selectivity to GVL within 1 h. IPA is found to be better solvent for levulinic acid (LA) to gamma-valerolactone (GVL) conversion, while substantial leaching of iron takes place when water is used as a solvent. It is observed that bimetallic sites are responsible for reduction of LA, while strong acidic sites of MMT are favoring subsequent cyclization to GVL. XPS analysis of fresh and reused Fe-Ni/MMT composites suggest that the catalyst surface does not undergo any chemical change during successive cycles, and the catalytic activity is retained up to six cycles. The plausible mechanism for LA to GVL conversion involves reductive cyclization processes through formation of levulinate ester that undergoes lactonization due to synergism in bimetallic nanoparticles and MMT clay.